"The Enemy of the People": Populists and Press Freedom. (June 2020) - Kenny, Paul D.
To what extent is populist rule associated with a decline in press freedom and freedom of expression? Populist rule refers to government headed by charismatic leaders who seek to gain and retain power by mobilizing mass constituencies that are typically free of other political attachments. Populism in this sense matters for two reasons: (1) controlling the media is a core objective of populists compared with other types of political leaders, who can rely on other organizational links to supporters; and (2) the interests of populist parties are virtually equivalent to the interests of party leaders, which means that populists face different time horizons and constraints on their behavior than the leaders of more deeply institutionalized parties. Using cross-national data on up to ninety-one countries from 1980 to 2014, this paper tests whether populist rule is associated with the erosion of press freedom and freedom of expression relative to other types of government and whether any effect is conditional on the ideology of the populist government in question. It finds that populist rule is associated with a decline in most measures of media freedom relative to programmatic party rule. However, this effect is lessened for right-leaning populist governments.